Distinct roles of α‐ and β‐tubulin polyglutamylation in controlling axonal transport and in neurodegeneration. (26th July 2021) - Bodakuntla, Satish; Yuan, Xidi; Genova, Mariya; Gadadhar, Sudarshan; Leboucher, Sophie; Birling, Marie‐Christine; Klein, Dennis; Martini, Rudolf; Janke, Carsten; Magiera, Maria M
Abstract: Tubulin polyglutamylation is a post‐translational modification of the microtubule cytoskeleton, which is generated by a variety of enzymes with different specificities. The "tubulin code" hypothesis predicts that modifications generated by specific enzymes selectively control microtubule functions. Our recent finding that excessive accumulation of polyglutamylation in neurons causes their degeneration and perturbs axonal transport provides an opportunity for testing this hypothesis. By developing novel mouse models and a new glutamylation‐specific antibody, we demonstrate here that the glutamylases TTLL1 and TTLL7 generate unique and distinct glutamylation patterns on neuronal microtubules. We find that under physiological conditions, TTLL1 polyglutamylates α‐tubulin, while TTLL7 modifies β‐tubulin. TTLL1, but not TTLL7, catalyses the excessive hyperglutamylation found in mice lacking the deglutamylase CCP1. Consequently, deletion of TTLL1, but not of TTLL7, prevents degeneration of Purkinje cells and of myelinated axons in peripheral nerves in these mice. Moreover, loss of TTLL1 leads to increased mitochondria motility in neurons, while loss of TTLL7 has no such effect. By revealing how specific patterns of tubulin glutamylation, generated by distinct enzymes, translate into specific physiological and pathological readouts, we demonstrate the relevance of the tubulin code for homeostasis. SYNOPSIS: Polyglutamylation is a posttranslational modification of tubulin that is highly enriched in neurons. Here we demonstrate that two neuronal polyglutamylases, TTLL1 and TTLL7, have distinct enzymatic activities, which generate unique patterns of polyglutamylation in vivo . We find that TTLL1, but not TTLL7 affects mitochondria transport and neuronal survival, in both central and peripheral nervous system. TTLL1 polyglutamylates α‐tubulin, while TTLL7 modifies β‐tubulin in vivo . In the absence of the deglutamylase CCP1, excessive polyglutamylation leading to neurodegeneration is generated by TTLL1, but not by TTLL7. Degeneration of neurons in both, central and peripheral nervous system, can be avoided by inactivating TTLL1, but not TTLL7. Polyglutamylation generated by TTLL1, but not by TTLL7 affects mitochondria mobility in axons of hippocampal neurons. Abstract : New mouse models and modification‐specific antibodies reveals that tubulin glutamylases TTLL1 and TTLL7 generate unique glutamylation patterns on neuronal microtubules, which regulate mitochondria motility and neuronal survival.